Gambaran Interaksi Obat Pada Pasien Diabetes Mellitus Tipe 2 di Rumah Sakit X - Fajrin Noviyanto; Rita Mintarsih; Farahdina Chairani (State University of Gorontalo, 2023)
Diabetes mellitus is a chronic condition characterized by higher than normal blood glucose levels and problems with protein, carbohydrate, and lipid metabolism caused by a relative or total lack of the hormone insulin. In addition, as a result of more prescriptions being written, the danger of drug interactions increases due to potential interactions among diabetic inpatients. The purpose of this study was to describe drug interactions in patients with Type 2 Diabetes Mellitus at X Hospital in the period January-March 2023. Data taken retrospectively from medical records were used in this kind of study, and Lexicomp Interact Online was used to evaluate drug interaction data. The results of this study showed that females 46-55 experienced. Most drug interactions in the hospital. Based on lexicomp interact online, drug interactions were categorized into 3 categories, B minor (23.6%), C moderate (62.5%) and D major (13.9%). This study may encourage healthcare workers to increase their awareness to counteract drug interactions in diabetic patients with complications to improve their clinical outcomes.